2016
DOI: 10.1016/j.annemergmed.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Alcohol Use Among Injured Adult Patients Presenting to a Ghanaian Emergency Department

Abstract: Objective Injuries are the cause of almost six million deaths annually worldwide, with 15–20% alcohol-associated. The frequency of alcohol-associated injury varies among countries, and is unknown in Ghana. We determined the frequency of positive alcohol tests among injured adults in a Ghanaian Emergency Department (ED). Methods This is a cross-sectional chart review of consecutive injured patients 18 years or older presenting to the Komfo Anokye Teaching Hospital ED for care within eight hours of injury. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…In this study, just over one fifth of adults (20.6%) presenting with injuries to the emergency departments of the four largest hospitals in Trinidad and Tobago self-reported the consumption of alcohol within the six hours prior to their injury. This figure is midway within the range of 7–38% reported by other countries globally and in Latin America and the Caribbean [ 11 , 12 , 13 , 14 ]. As found in these prior studies, males and younger persons were over-represented among those with alcohol-related injuries.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, just over one fifth of adults (20.6%) presenting with injuries to the emergency departments of the four largest hospitals in Trinidad and Tobago self-reported the consumption of alcohol within the six hours prior to their injury. This figure is midway within the range of 7–38% reported by other countries globally and in Latin America and the Caribbean [ 11 , 12 , 13 , 14 ]. As found in these prior studies, males and younger persons were over-represented among those with alcohol-related injuries.…”
Section: Discussionsupporting
confidence: 57%
“…We have also noted from a previous study that the results of positive alcohol testing among injured patients in the ED were higher than what might be expected when considering the WHO data on alcohol use in Ghana 6. Studies from other African countries have shown that harmful alcohol use among injured patients in the ED was higher than that in the general population estimates 2 4 5.…”
Section: Discussionsupporting
confidence: 45%
“…Assessment of alcohol use characteristics among injured patients has been limited in large regions of the world, including Africa 4 5. We recently found that 35% of injured adults presenting to a Kumasi, Ghana, emergency department (ED) had positive alcohol breath tests or saliva tests 6. Using subject self-report, the WHO describes below-average per capita alcohol consumption in Ghana compared with the WHO Africa region 2.…”
Section: Introductionmentioning
confidence: 99%
“…Some countries, such as Brazil (Gjerde et al, 2015) have contributed with a large number of research studies (Pechansky et al, 2010) but for most countries the evidence is scattered and not comparable. Most importantly, there is a paucity of evidence on the presence of alcohol in RTIs among pedestrians and non-driver riders, who are important victims of RTIs(du Plessis et al, 2016; Forson et al, 2016; Maximus et al, 2016; Senserrick et al, 2014; Sethi et al, 2016; Waller et al, 1986). …”
Section: Introductionmentioning
confidence: 99%